A MATLAB-Linked Solver to Find Fuel Depletion in a PWR, a Suggested VVER-1000 Type. (15th March 2010) - Faghihi, F.; Saidi Nezhad, M.
Abstract : Coupled first-order IVPs are frequently used in many parts of engineering and sciences. We present a "solver" including three computer programs which were joint with the MATLAB software to solve and plot solutions of the first-order coupled stiff or nonstiff IVPs. Some applications related to IVPs are given here using our MATLAB-linked solver. Muon catalyzed fusion in a D-T mixture is considered as a first dynamical example of the coupled IVPs. Then, we have focused on the fuel depletion in a suggested PWR including poisons burnups (xenon-135 and samarium-149), plutonium isotopes production, and uranium depletion.